(untitled) (Bodhi Path, 2023)
As George Orwell has rightly said, ‘the most effective way to destroy people is to deny and obliterate their understanding of their history’. The history of India till a few years back displayed the insights of the victorious or those in power. With the approach of subaltern writings becoming popular we now have the history of the ones who were equally integral parts of the system, but were marginalised and had no representation in the documentation. Their discontent and contribution equally faced neglect. The history of labour in India is one such area which needs further exploration and a micro approach to documenting the facts and figures based on social stratification. The textile industry of Bombay (now Mumbai) generally offers us the vibrant history of the capitalists’ class, the European entrepreneurs, the indigenous mercantile class, the trade union leaders, the various legislations and Acts about the factories etc, but it has a void which needs to be filled now. The working class movement always had a broad classification, based on the haves and the haves not’s, as the workers were collectively defined as the marginalised. The fact remained that in our Indian society, the marginalisation further percolates to the layer of the caste system. The larger framework of the worker’s struggles against their exploitative masters conveniently overshadowed the struggle of the Dalits or the members of the lowest strata against their Hindu brethren. The textile mills were inaugurated in Bombay in the 1860s and they soon opened a plethora of opportunities for migration and employment to the inhabitants of rural India. This systematic migration was controlled and channelized by the Jobbers who were the recruiting agents between the mills and the workers. The history of the workers has found narration and voices through various research angles, but the discrimination and the treatment of alienation felt by the Dalits in this new industrial age have lost their place in this transition. As Herodotus rightly observed, ‘very few things happen at the right time and the rest do not happen at all, the conscientious historian will correct these defects’. This paper will attempt to document this forgotten history of the role and the contribution of the Dalits in the development of the textile era in Bombay. The paper will primarily focus on the issues and challenges which they faced in availing the equal growth opportunities. It will also argue the role of Jobbers, who is from a specific caste, systematically alienated the Dalits and allowed the exclusive growth of certain communities. Though the social fabric of the city of Bombay was changing and there was no dearth of socio-economic upliftment for all, still we find these practices groping the newly urbanised society. The Royal Commission of Labour of 1931 also reported the migratory patterns and the positional status of members of various castes and regions in their study. The economic thoughts of Dr Babasaheb Ambedkar will be the base of this paper and it would have strong reflections on his attempt to bring about socio-economic equity amongst the workers by taking up their cause systematically and paving the way for them constitutionally as well. The restructuring of society is only possible when we have an equal distribution of profits and this was perhaps what Dr Ambedkar strongly advocated. The paper will analyse his speeches and writings to develop his school of thought on the economic condition of India and safeguarding the rights of the dalit workers in India. To aptly quote Thomas Paine ‘we have it in our power to begin the world over again’.